Popular education with dialogue rounds: Soft technologies as a power in promoting health in the elderly in the community (Research, Society and Development, 2023)
Health education through popular education enables a simple and fluid dialogue with the community, promoting the subject's autonomy as a participant in the process. This experience report aims to present the experience of a Multiprofessional Residency team in family and community health in Piauí, linked to a Basic Health Unit, in the development of activities based on popular health education, based on circle dialogue, methodologies activities and playfulness in a social center, as a successful experience in health promotion. This research is qualitative with a descriptive approach on a group created for health education activities, which takes place every fortnight, has existed for a year and a half and has an average of 15 participants, each meeting has a theme focused on health promotion and some therapeutic practice or PICS. The results were very satisfactory, with the public always assiduous and frequently reporting the positive influence that the activities carried out had on their health and well-being. Thus, the importance of experiences that promote health in an active and dynamic way is observed, with more user inclusion and participation within the health education process. Health education along the lines of popular education makes learning more attractive, easier and efficient for the user, being considered a relevant means of providing health education in the community.